2009
DOI: 10.1002/ejic.200900772
|View full text |Cite
|
Sign up to set email alerts
|

1,1′‐Diborylferrocenes from [2]Boraferrocenophanes by Boron–Boron Exchange

Abstract: The reactivity of [2]boraferrocenophane [(η5‐C5H4)–BNMe2–BNMe2–(η5‐C5H4)Fe] (3) with borane and diborane compounds was examined, resulting in the complete loss of the–BNMe2–BNMe2– bridge and the concomitant formation of 1,1′‐borylated ferrocenes. With this unprecedented reactivity pattern, an alternative access to this class of compounds is established.(© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2009)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…After 24 h, the reaction was complete in each case and the color changed from red to orange (Scheme 5). After workup, the 1,3-dibora-2-thia [3]ferrocenophane (10) and the 1,3-dibora-2-selena [3]ferrocenophane (11) were isolated in 63% and 65% yield, respectively, and their constitution in solution was confirmed by multinuclear NMR spectroscopy. Both compounds were initially synthesized via a ring-closure reaction, starting from 1,1 0 -bis[chloro(dimethylamino)boryl]ferrocene and reaction with either Li 2 S or Li 2 Se, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…After 24 h, the reaction was complete in each case and the color changed from red to orange (Scheme 5). After workup, the 1,3-dibora-2-thia [3]ferrocenophane (10) and the 1,3-dibora-2-selena [3]ferrocenophane (11) were isolated in 63% and 65% yield, respectively, and their constitution in solution was confirmed by multinuclear NMR spectroscopy. Both compounds were initially synthesized via a ring-closure reaction, starting from 1,1 0 -bis[chloro(dimethylamino)boryl]ferrocene and reaction with either Li 2 S or Li 2 Se, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Subsequently, we reported an alternative synthesis of 5, its crystal structure, and initiated reactivity studies of this compound, revealing distinct, and to some extent surprising reactivity patterns [10]. Thus, in the presence of either boranes or diboranes, the formation of 1,1 0 -diborylferrocenes was observed [11]. In addition, the reactivity towards multiple bond systems was examined and it was demonstrated that in the presence of the platinum phosphine complex [Pt(PEt 3 ) 3 ], the homogeneous transition metal catalyzed diboration of alkynes proceeded.…”
Section: Introductionmentioning
confidence: 93%
“…111 The transition-metal-mediated mechanism, which involves insertion of the NN bond of azobenzene into the B− B bridge of 47 to afford the corresponding [4]ferrocenophane, is believed to be facilitated by the inherent ring strain in this species. Finally, cleavage of the Cp ipso −B bond has been achieved through 112 (c). Diphospha [2]ferrocenophanes.…”
Section: Recent Work On Strained [2]ferrocenophanesmentioning
confidence: 99%
“…Only few other channels of reactivity have been reported in the literature for [2]borametalloarenophanes so far. These include chalcogen insertion into the strained B–B bond of [2]boraferrocenophane 33 ,45 and one example, in which complete degradation of the diboron ansa ‐bridge of 33 occurred 46. Since the pronounced reactivity of chalcogens towards Sn–Sn bonds was well‐established, we reasoned that a similar reactivity might also be amenable for strained B–B bond linkages found in ansa ‐bridged sandwich systems.…”
Section: Other Reactionsmentioning
confidence: 99%
“…The last reaction pathway might be considered a special case, since it is a unique example for C ipso –B bond cleavage in [ n ]borametalloarenophane chemistry 46. More importantly, degradation of the ansa ‐bridge did not result in the formation of ferrocene or other degradation products, but selectively generated the 1,1′‐bis(boryl) ferrocenes 79 and 80 .…”
Section: Other Reactionsmentioning
confidence: 99%